Gene conversion and linkage: effects on genome evolution and speciation. Issue 1 (29th July 2016) - Korunes, Katharine L.; Noor, Mohamed A. F.
Abstract: Crossing over is well known to have profound effects on patterns of genetic diversity and genome evolution. Far less direct attention has been paid to another distinct outcome of meiotic recombination: noncrossover gene conversion (NCGC). Crossing over and NCGC both shuffle combinations of alleles, and this degradation of linkage disequilibrium (LD) has major evolutionary consequences, ranging from immediate effects on nucleotide diversity to long‐term consequences that shape genome evolution, species formation and species persistence. Unlike simple crossing over, NCGC has the potential to alter allele frequencies. Gene conversion can also occur in genomic regions where crossing over does not, and it purportedly exhibits more uniform rates across genomes. Considerable progress has been made towards understanding the mechanisms of gene conversion, and this progress enables us to begin exploring how gene conversion affects processes such as molecular evolution and interspecies gene flow. These topics are timely with the recent shift in focus from a primarily neutral null model of molecular evolution and speciation to one incorporating base levels of selection, making it all the more crucial to understand the basis and evolutionary implications of linkage. Here, we discuss the impact of gene conversion on genome structure and evolution and the current methods for detecting these events. We provide a comprehensive review of how gene conversion breaks down LD and affects both short‐ and long‐term evolutionary processes, and we contrast its impact to that expected from crossing over alone.